Familial early puberty: presentation and inheritance pattern in 139 families. Issue 1 (December 2016) - Durand, Adélaïde; Bashamboo, Anu; McElreavey, Ken; Brauner, Raja
Abstract Background The mechanism that initiates the onset of puberty is largely unknown but the age of onset is mainly under genetic control and influenced by environmental factors including nutrition. The coexistence in the same family of central precocious puberty and advanced puberty, both representing early puberty, suggests that they may represent a clinical spectrum of the same trait due to early activation of the GnRH pulse generator. We therefore evaluated the mode of inheritance of early puberty in a large series of familial cases. Methods A retrospective, single center study was carried out on 154 probands (116 girls and 38 boys), from 139 families seen for idiopathic central precocious puberty (onset before 8 years in girls and 9–10 years in boys, n = 93) and/or advanced puberty (onset between 8 and 10 years in girls and 10 and 11 years in boys, n = 61) seen over a period of 8 years. Results Of the 139 families, 111 (80.4 %) had at least one affected 1st degree relatives, 17 (12 %) had only 2nd, 5 (3.6 %) only 3rd and 3 (2.2 %) had both 2nd and 3rd degree affected individuals. In the two remaining families, the unaffected mother had affected girls from two unaffected fathers. In the majority of families the inheritance of the phenotype was consistent with autosomal dominant mode of transmission with incomplete penetrance. An exclusively maternal mode of transmission could be observed or inferred in 83 families, paternal in only 2 families (p < 0.0001) and both maternal and paternal modes in 15 families. In the 139 families, 374 cases of early puberty were identified of whom 315 (84.2 %) were affected females and 59 (15.8 %) affected males (p < 0.0001). Twenty one percent of families had exclusively precocious puberty, 25 % had exclusively advanced puberty and 54 % had combinations of both. Conclusions The data confirm the high incidence of affected girls with familial early puberty. The mode of inheritance of the phenotype is predominantly maternal. More than half of the families included both precocious and advanced puberty suggesting similar genetic factors.